MENGUNGKAP MORAL HAZARD PADA AKAD MURABAHAH AL-WAKALA DI SEBUAH BANK SYARIAH DI PROVINSI GORONTALO - Sri Apriyanti Husain; Unti Ludigdo; Noval Adib (Trunojoyo University of Madura, 2017)
Sharia banks as part of Islamic financial institutions are inseparable from moral hazard practices. Moral hazard is an act born from the existence of information asymmetry. This study aims to explore how customers and employees perform moral hazard on murabahah al-wakalah in a Syariah Bank in Gorontalo Province. This research uses etnometodology as a research methodology. using etnometodology is because etnometodology is a suitable methodology to reveal how customers and employees perform moral hazard on murabahah al-wakalah in a Syariah Bank in Gorontalo Province. Moral hazard that occurs in a Sharia Bank in Gorontalo Province is conducted by banks and financing customers. Moral hazard conducted by the bank first, the bank does not provide transparency akad used. Second, banks do not provide transparency of product financing information. Third, banks are more concerned with customer installments. Fourth, banks do not conduct monitoring and evaluation. Fifth, the bank only asks the customer just to sign without explaining to the customer